Compartment-dependent mitochondrial alterations in experimental ALS, the effects of mitophagy and mitochondriogenesis - Natale, Gianfranco; Lenzi, Paola; Lazzeri, Gloria; Falleni, Alessandra; Biagioni, Francesca; Ryskalin, Larisa; Fornai, Francesco (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic lateral sclerosis (ALS) is characterized by massive loss of motor neurons. Data from ALS patients and experimental models indicate that mitochondria are severely damaged within dying or spared motor neurons. Nonetheless, recent data indicate that mitochondrial preservation, although preventing motor neuron loss, fails to prolong lifespan. On the other hand, the damage to motor axons plays a pivotal role in determining both lethality and disease course. Thus, in the present article each motor neuron compartment (cell body, central, and peripheral axons) of G93A SOD-1 mice was studied concerning mitochondrial alterations as well as other intracellular structures. We could confirm the occurrence of ALS-related mitochondrial damage encompassing total swelling, matrix dilution and cristae derangement along with non-pathological variations of mitochondrial size and number. However, these alterations occur to a different extent depending on motor neuron compartment. Lithium, a well-known autophagy inducer, prevents most pathological changes. However, the efficacy of lithium varies depending on which motor neuron compartment is considered. Remarkably, some effects of lithium are also evident in wild type mice. Lithium is effective also in vitro, both in cell lines and primary cell cultures from the ventral spinal cord. In these latter cells autophagy inhibition within motor neurons in vitro reproduced ALS pathology which was reversed by lithium. Muscle and glial cells were analyzed as well. Cell pathology was mostly severe within peripheral axons and muscles of ALS mice. Remarkably, when analyzing motor axons of ALS mice a subtotal clogging of axoplasm was described for the first time, which was modified under the effects of lithium. The effects induced by lithium depend on several mechanisms such as direct mitochondrial protection, induction of mitophagy and mitochondriogenesis. In this study, mitochondriogenesis induced by lithium was confirmed in situ by a novel approach using [2-3H]-adenosine.